Anodic TiO2 nanotube layers: Why does self-organized growth occur-A mini review - Zhou, Xuemei; Nguyen, Nhat Truong; Özkan, Selda; Schmuki, Patrik (Electrochemistry Communications, 2014)
The present review gives an overview of the highlights of more than 10 years of research on synthesis and applications of ordered oxide structures (nanotube layers, hexagonal pore arrangements) that are formed by self-organizing anodization of metals. In particular we address the questions after the critical factors that lead to the spectacular self-ordering during the growth of anodic oxides that finally yield morphologies such as highly ordered TiO2 nanotube arrays and similar structures. Why are tubes and pores formed-what are the key parameters controlling these processes?
EAM Import::2019-03-13

Boron-doped diamond (BDD) as an efficient back contact to thermally grown TiO2 photoelectrodes - Özkan, Selda; Ghanem, Hanadi; Mohajernia, Shiva; Hejazi, Seyedsina; Fromm, Timo; Borchardt, Rudolf; Rosiwal, Stefan; Schmuki, Patrik (ChemElectroChem, 2019)
In the present work, we investigate the efficiency of TiO2 photoelectrode layers on boron-doped diamond foil (BDDF) in comparison with a classic conducting glass (fluorine-doped tin oxide, FTO) back contact. Crystalline thin TiO2 layers were prepared on the substrates by two different methods: (i) deposition of metallic Ti thin films followed by thermal oxidation to form TiO2 (TO-TiO2), (ii) reactive sputter deposition of TiO2 thin films and crystallization of these layers (SP-TiO2). Optimized layers show that TO-TiO2 films on BDDF deliver a significantly higher incident photon to current ifficiency (IPCE) compared to directly sputtered SP-TiO2 layers and these layers on BDDF also outperform FTO as a back contact. We ascribe this beneficial effect of the BDDF back contact to the formation of an intermediate conductive phase of Ti-carbides at the TO-TiO2/BDDF interface.

Extracting the limiting factors in photocurrent measurements on TiO2 nanotubes and enhancing the photoelectrochemical properties by Nb doping - Özkan, Selda; Mazare, Anca Valentina; Schmuki, Patrik (Electrochimica Acta, 2015)
In the present work, we extract the key factors that influence and limit the photoresponse of anodic TiO2 nanotubular layers. For this we formed nanotube layers of different thicknesses, annealed the structures at different temperatures and evaluated the doping effect of Nb. Using various analytical characterization tools (SEM, XRD, XPS, ToF-SIMS), we found that a most crucial impact on limiting the photoresponse in nanotubular layers is the formation of a rutile layer at the metal/oxide interface during the thermal annealing process (by thermal oxidation of Ti metal underneath tubes). This rutile layer increases severely in thickness with annealing temperature. We show that this detrimental effect can be overcome by doping the TiO2 NTs with very low amounts of Nb (0.1 at% Nb), which can result in a 12-fold increase of the IPCE for high temperature annealed TiO2 NTs.
EAM Import::2019-03-14

Lateral spacing of TiO2 nanotubes modulates osteoblast behavior - Necula, Madalina Georgiana; Mazare, Anca Valentina; Ion, Raluca Nicoleta; Özkan, Selda; Park, Jung; Schmuki, Patrik; Cimpean, Anisoara (Materials, 2019)
Titanium dioxide (TiO2) nanotube coated substrates have revolutionized the concept of implant in a number of ways, being endowed with superior osseointegration properties and local drug delivery capacity. While accumulating reports describe the influence of nanotube diameter on cell behavior, little is known about the effects of nanotube lateral spacing on cells involved in bone regeneration. In this context, in the present study the MC3T3-E1 murine pre-osteoblast cells behavior has been investigated by using TiO2 nanotubes of 78 nm diameter and lateral spacing of 18 nm and 80 nm, respectively. Both nanostructured surfaces supported cell viability and proliferation in approximately equal extent. However, obvious differences in the cell spreading areas, morphologies, the organization of the actin cytoskeleton and the pattern of the focal adhesions were noticed. Furthermore, investigation of the pre-osteoblast differentiation potential indicated a higher capacity of larger spacing nanostructure to enhance the expression of the alkaline phosphatase, osteopontin and osteocalcin osteoblast specific markers inducing osteogenic differentiation. These findings provide the proof that lateral spacing of the TiO2 nanotube coated titanium (Ti) surfaces has to be considered in designing bone implants with improved biological performance.
CRIS-Team Scopus Importer:2019-10-01
Keywords: Cell adhesion and morphology; Cell proliferation; Osteoblast; Osteogenic differentiation; Spaced TiO

Li+ doped anodic TiO2 nanotubes for enhanced efficiency of Dye-sensitized solar cells - Cha, Gi; Özkan, Selda; Hwang, Imgon; Mazare, Anca Valentina; Schmuki, Patrik (Surface Science, 2022)
The insertion of cations such as H+ and Li+ to TiO2 photoelectrodes is a universally recognized method to enhance the electric conductivity of TiO2 electrodes. In the present work we report on the fabrication and use of Li+ inserted TiO2 nanotubes (NTs) as a photoanode scaffold in dye-sensitized solar cells (DSSCs). Li+ was successfully inserted into the TiO2 NTs by a cathodic treatment in 1 M LiClO4/ethylene carbonate (EC) electrolyte. We observe for DSSCs fabricated from such nanotubes an overall solar cell efficiency of ∼7.1% compared to an efficiency of ∼5.7% for the non Li-intercalated electrode. We ascribe this enhancement to a faster electron transport and an increased conductivity in the lithiated TiO2 NTs.
CRIS-Team Scopus Importer:2022-01-07
Keywords: Anodization; Dye-sensitized solar cell (DSSC); Li ion intercalation; TiO

Macrophage‐like Cells Are Responsive to Titania Nanotube Intertube Spacing—An In Vitro Study - Necula, Madalina Georgiana; Mazare, Anca Valentina; Negrescu, Andreea Mariana; Mitran, Valentina; Özkan, Selda; Trusca, Roxana; Park, Jung; Schmuki, Patrik; Cimpean, Anisoara (International Journal of Molecular Sciences, 2022)
With the introduction of a new interdisciplinary field, osteoimmunology, today, it is well acknowledged that biomaterial‐induced inflammation is modulated by immune cells, primarily macrophages, and can be controlled by nanotopographical cues. Recent studies have investigated the effect of surface properties in modulating the immune reaction, and literature data indicate that various surface cues can dictate both the immune response and bone tissue repair. In this context, the purpose of the present study was to investigate the effects of titanium dioxide nanotube (TNT) interspacing on the response of the macrophage‐like cell line RAW 264.7. The cells were maintained in contact with the surfaces of flat titanium (Ti) and anodic TNTs with an intertube spacing of 20 nm (TNT20) and 80 nm (TNT80), under standard or pro‐inflammatory conditions. The results revealed that nanotube interspacing can influence macrophage response in terms of cell survival and proliferation, cellular morphology and polarization, cytokine/chemokine expression, and foreign body reaction. While the nanostructured topography did not tune the macrophages’ differentiation into osteoclasts, this behavior was significantly reduced as compared to flat Ti surface. Overall, this study provides a new insight into how nanotubes’ morphological features, particularly intertube spacing, could affect macrophage behavior.
CRIS-Team Scopus Importer:2022-04-22
Keywords: Cytokines; Inflammation; Intertube spacing; Macrophage; Osteoclastogenesis; TiO2 nanotubes

Multi-Leg TiO(2)Nanotube Photoelectrodes Modified by Platinized Cyanographene with Enhanced Photoelectrochemical Performance - Shahrezaei, Mahdi; Hejazi, Seyyed Mohammad Hossein; Rambabu, Yalavarthi; Vavrecka, Miroslav; Bakandritsos, Aristides; Özkan, Selda; Zboril, Radek; Schmuki, Patrik; Naldoni, Alberto; Kment, Stepan (Catalysts, 2020)
Highly ordered multi-leg TiO(2)nanotubes (MLTNTs) functionalized with platinized cyanographene are proposed as a hybrid photoelectrode for enhanced photoelectrochemical water splitting. The platinized cyanographene and cyanographene/MLTNTs composite yielded photocurrent densities 1.66 and 1.25 times higher than those of the pristine MLTNTs nanotubes, respectively. Open circuit V(OC)decay (V-OCD), electrochemical impedance spectroscopy (EIS), and intensity-modulated photocurrent spectroscopy (IMPS) analyses were performed to study the recombination rate, charge transfer characteristics, and transfer time of photogenerated electrons, respectively. According to the V(OCD)and IMPS results, the addition of (platinized) cynographene decreased the recombination rate and the transfer time of photogenerated electrons by one order of magnitude. Furthermore, EIS results showed that the (platinized) cyanographene MLTNTs composite has the lowest charge transfer resistance and therefore the highest photoelectrochemical performance.
CRIS-Team WoS Importer:2020-08-14

Optimized Polymer Electrolyte Membrane Fuel Cell Electrode Using TiO2 Nanotube Arrays with Well-Defined Spacing - Özkan, Selda; Valle, Francesco; Mazare, Anca Valentina; Hwang, Imgon; Taccardi, Nicola; Zazpe, Raul; Macak, Jan M.; Cerri, Isotta; Schmuki, Patrik (ACS Applied Nano Materials, 2020)
TiO2-based catalyst supports in polymer electrolyte membrane fuel cells (PEMFCs) are widely investigated and provide an alternative to corrosion-susceptible carbon-based catalyst supports. For PEMFCs, designing a catalyst support material with an optimal geometry is of high importance to provide high catalyst dispersion, long-term operation, and efficient fuel cell performance. In this work, we report on the use of spaced (SP) TiO2 nanotubes (NTs) as catalyst support for the cathode electrode of PEMFCs. We construct a vertically aligned Pt-TiO2 NT catalyst layer on the Nafion membrane by a threestep process: (i) growth of self-organized TiO2 nanotubes with defined intertube spacing and detachment from the Ti substrate, (ii) Pt catalyst decoration on tube walls by atomic layer deposition (ALD) or photodeposition (PD), and (iii) decal transfer of the Pt-TiO2 catalyst layer onto Nafion to fabricate a membraneelectrode assembly (MEA) by hot pressing. Such an MEA configuration based on vertically aligned high aspect ratio spaced TiO2 nanotubes with Pt catalyst decoration delivers a significantly higher fuel cell performance, compared with close-packed (CP) TiO2 nanotubes. The key for this excellent performance is that TiO2 NTs with a regular interspacing on the Nafion polymer membrane enable highly dispersed Pt catalyst decoration and provide strongly enhanced mass transport in the interspaces.
CRIS-Team WoS Importer:2020-06-19

Self-induced current oscillations during anodization of Ti in LA containing DMSO electrolyte - Özkan, Selda; Mazare, Anca Valentina; Schmuki, Patrik (Electrochemistry Communications, 2016)
During self-organized nanotubular oxide growth by electrochemical anodization of Ti in lactic acid (LA) containing dimethyl sulfoxide (DMSO) electrolytes, we observe the occurrence of regular current oscillations (COs). Key factors that influence COs are the LA concentration, the surface roughness and diffusion limitation. The oscillation characteristics (amplitude and period) depend on both LA concentration and applied voltage. Under optimized oscillation conditions a sequential growth/detachment of the TiO2 layers is observed that leads to a self-stacking of TiO2 nanostructured multilayers.
EAM Import::2019-03-13